The Effectiveness Of Web-Based Climate Change Education On Improving Climate Change Literacy Of Primary School Students - Perumal, Mariayee (2023)
Climate Change Literacy is seen as an essential part of the teaching and learning of Science. Fostering climate change literacy is closely related to content delivery and the teaching strategy used in Science-based subject, particularly at the primary school level. This study was conducted with the aim to measure the effectiveness of Web-based Climate Change Education on improving climate change literacy among primary school students’ knowledge (greenhouse effect, global warming, ozone layer depletion and acid rain), values (egocentric, homocentric and ecocentric), belief (new-ecological paradigm, attribute to responsibility and awareness of consequences), personal norms, and pro-environmental behaviour to conserve the climate. This study used a mixed method concurrent embedded research approach that incorporates both quantitative and qualitative data collection in which qualitative data was embedded within the quantitative data. Questionnaire survey and interviews were conducted to measure the changes in the dependent variables. The Climate Change Literacy Questionnaire was used to measure the effectiveness of Web-based Climate Change Education on students’ knowledge, values, belief, personal norms, and pro-environmental behaviour to conserve the climate.